Management of Lowe syndrome: a case report - Risky Vitria Prasetyo; Heru Setiawan; Ninik Asmaningsih Soemyarso; Mohammad Sjaifullah Noer; Irwanto Irwanto; Prastiya Indra Gunawan; Rozalina Loebis; Sri Andreani Utomo; Ni Wayan Tirthaningsih (Paediatrica Indonesiana, 2015)
Lowe syndrome (the oculocerebrorenal syndrome of Lowe, OCRL) is a multisystem disorder characterized by anomalies affecting the eyes, nervous system and kidneys.1-3 The disorder was first recognized by Lowe et al. in 1952, and described as a unique syndrome with organic aciduria, decreased renal ammonia production, hydrophthalmos, and mental retardation. In 1954, renal Fanconi syndrome was recognized as being associated with Lowe syndrome and in 1965, a recessive X-linked pattern of inheritance was determined.2,4 Lowe syndrome is a very rare disease, with an estimated prevalence in the general population of 1 in 500,000. According to the Lowe Syndrome Association (LSA) in the USA, the estimated prevalence is between 1 and 10 affected males in 1,000,000 people, with 190 living in the year 2000. The Italian Association of Lowe Syndrome estimated that there were 34 Lowe syndrome patients (33 boys and one girl) living in Italy in the year 2005.2,4,5 It almost exclusively affects males.6 Physicians may not be familiar with Lowe syndrome due to its rarity.4